Prolonged Active Prone Positioning in Spontaneously Breathing Non-intubated Patients With COVID-19-Associated Hypoxemic Acute Respiratory Failure With PaO2/FiO2 >150 - Pierucci, Paola; Ambrosino, Nicolino; Di Lecce, Valentina; Dimitri, Michela; Battaglia, Stefano; Boniello, Esterina; Portacci, Andrea; Resta, Onofrio; Carpagnano, Giovanna Elisiana (Frontiers in Medicine, 2021)
Background: The COVID-19 pandemic has led to new approaches to manage patients outside the ICU, including prone positioning in non-intubated patients. Objectives: To report the use of prolonged active prone positioning in spontaneously breathing patients with COVID-19-associated acute respiratory failure. Spontaneously breathing vs non-invasive respiratory support for COVID19 associated acute respiratory failure. Methods: Patients with PaO2/FiO2 > 150, with lung posterior consolidations as assessed by means of lung ultrasound, and chest x-ray were studied. Under continuous pulse oximetry (SpO2) monitoring, patients maintained active prone position. A PaO2/FiO2 < 150 was considered as treatment failure and patients had to be switched to non-invasive respiratory support. Retrospectively, data of 16 patients undergoing who refused proning and underwent non-invasive respiratory support were used as controls. The primary outcome was the proportion of patients maintaining prolonged prone position and discharged home. Secondary outcomes included improvement in oxygenation, hospital length of stay, and 6-month survival. Results: Three out of 16 (18.7%) patients did not tolerate the procedure. Three more patients showed a worsening in PaO2/FiO2 to <150 and required non-invasive support, two of whom finally needing endotracheal intubation. After 72 h, 10 out of 16 (62.5%) patients improved oxygenation [PaO2/FiO2: from 194.6 (42.1) to 304.7 (79.3.2) (p < 0.001)] and were discharged home. In the control group, three out of 16 failed, required invasive ventilatory support, and died within 1 month in ICU. Thirteen were successful and discharged home. Conclusion: In non-intubated spontaneously breathing COVID-19 patients with PaO2/FiO2 >150, active prolonged prone positioning was feasible and tolerated with significant improvement in oxygenation.